O ensino de História nas séries finais do ensino fundamental: história local e memória - Leal, Leonardo Rodrigues (2021)
The main objective of this work is to create a product, which in this case is a paradidactic material, to be applied in the classroom with students and also to be offered to other teachers who are interested. The problem questions that guided the research were - Why then carry out a study on the neighborhood and the school? What do you intend to build from this research on these places? Local history presents itself as a starting point for historical learning and leads to an understanding of longer historical processes. The research is centered on the Itararé neighborhood, municipality of Santa Maria, which had its development and decay linked to the growth and fall of the 20th century railway system. This makes the neighborhood an open-air museum, as the architectural ensemble we find in the place tells us a lot about the importance that the neighborhood had in the development of the city of Santa Maria. In this way, the study of local history presents itself as a moment of critical reflection about the social reality and, mainly, as a reference for the process of formation of the identities of the subjects and their social groups. The proposal is to help in the qualification of history teachers. The product presented in the investigation was a Didactic Sequence (SD) for teaching local history in elementary school. The theme of didactic sequences has been gaining importance in educational studies, especially in view of the so-called active methodologies that deal with the role of students in the learning process. The activities conceived in the SD were partially implemented, as a result of the Covid-19 pandemic that prevented the proposed activities from being carried out, so that we still have to apply it in its entirety in order to verify its effectiveness with regard to the teaching/learning local history, and the results of this activity can be discussed in future works.